"Caught Between Two Worlds": Asian American Elementary Teachers' Enactment of Asian American History. Issue 2 (4th March 2019) - Naseem Rodríguez, Noreen
Abstract : Traditional narratives of U.S. history largely exclude Asian American histories, particularly at the elementary level. This qualitative case study examines how three Asian American elementary school teachers included Asian American histories in their social studies curriculum and scaffolded student understanding by sharing their own hybrid identities and experiences. The teachers (re)framed the purpose of the historical narrative and confronted the dominant narrative of Japanese American incarceration, while making connections between Japanese American incarceration and contemporary events. Through this work, the teachers illustrated the complexity of race in the United States and presented discrimination and racism as enduring issues worthy of discussion with young learners.